Surface roughness and micro-injection molding - Yao, Jing (2008)
The injection molding filling process of a micro cavity with a micro groove and two different surface roughness was studied experimentally under different process parameters. The process parameters investigated were the cavity thickness, shot size, injection rate, melt temperature, and mold temperature. The effects of the process parameters on the relationship between the advancing polymer melt front and the filling of the micro groove, and the relationship between the fillings of the two halves in the micro cavity with different surface roughness, were discussed.